Analysis of Long-Term Evolution (LTE) Propagation Pathloss Calculation and Pathloss Simulation in Lubuk Minturun Urban Village, Koto Tangah Sub-District, Padang - Syaza Ibra Harlin; Nadita Wijayani Putri; Nasrul; Siska Aulia; Azhar (Politeknik Negeri Padang, 2024)
Good signal quality is characterized by the small amount of propagation path loss or path loss that occurs. These propagation path losses can be caused by the distance between the site and the receiver (mobile station), transmitter frequency, natural conditions, and weather conditions. The farther between the site and the receiver (mobile station), the greater the propagation path loss. The use of propagation models in planning a site development in an area can predict or consider the value of propagation path losses, such as the Okumura-Hatta and COST-231 propagation models. Measurement of signal quality received by the receiver (mobile station) in the making of this final project using the drive test method. Determination of site coordinates in the measurement makes it easier to calculate the distance between the site and the mobile station. The calculation of the Okumura-Hatta propagation model and the COST-231 propagation model will produce a better-received power level value compared to the received power level value in the measurement. This is because the calculation only considers the distance between the site and the receiver (mobile station) without any obstacles or barriers, while the value generated during measurement will be influenced by distance, obstacles or barriers, earth contours, and weather conditions. One of them is Lubuk Minturun Village where the measurement of propagation path loss (Pathloss) is carried out due to the poor quality of the 4G Long Term Evolution (LTE) network.